2015
DOI: 10.1158/1078-0432.ccr-14-2792
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Deprivation Induces a Targetable Vulnerability in Triple-Negative Breast Cancer Cells by Enhancing TRAIL Receptor-2 Expression

Abstract: Purpose Many neoplasms are vulnerable to methionine deficiency by mechanisms that are poorly understood. Because gene profiling studies have revealed that methionine depletion increases TNF-related apoptosis-inducing ligand receptor-2 (TRAIL-R2) mRNA, we postulated that methionine stress sensitizes breast cancer cells to proapoptotic TRAIL-R2 agonists. Experimental Design Human triple (ER/PR/HER2)-negative breast carcinoma cell lines were cultured in control or methionine-free media. The effects of methionin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 38 publications
5
89
0
Order By: Relevance
“…Cell surface expression of TRAIL receptors (TRAIL-R1 and TRAIL-R2) was determined by flow cytometry using TRAIL-R1, TRAIL-R2, or control IgG1 mAb conjugated with allophycocyanin (BioLegend) as described previously [14].…”
Section: Trail Receptor Cell Surface Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell surface expression of TRAIL receptors (TRAIL-R1 and TRAIL-R2) was determined by flow cytometry using TRAIL-R1, TRAIL-R2, or control IgG1 mAb conjugated with allophycocyanin (BioLegend) as described previously [14].…”
Section: Trail Receptor Cell Surface Expressionmentioning
confidence: 99%
“…Real-time PCR for TRAIL-R1, TRAIL-R2, and GAPDH was performed as described previously [14]. Primers for XIAP (forward 5-AGTGCCACGCAGTCTACAAA, …”
Section: Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that methionine levels are directly involved in promoting proliferation of cancer cells [31] and in protecting the cancer cells against chemotherapeutic drugs like Fluorouracil [32]. Methionine deprivation has been shown to inhibit tumor cell growth in various cancers both in in vitro and in vivo models along with chemo-sensitizing cancer cells [33][34][35][36]. We observed decreased levels of methionine in resistant C200 cells, which could indicate its increased utilization ( Figure 3B), and could suggest the presence of 'methionine dependency' in the resistant cells.…”
Section: Discussionmentioning
confidence: 99%